Fresno County Bar Luncheon with State Bar President Dale Hanst - Watkins, Howard::::::::: (1984)
Fresno County Bar Association President Rodney Worrel, Fresno County Bar Association President-Elect Donald Fischbach (no mustache) Dale Hanst seated at head table Golden State Plaza Ballroom; coffee pot on glass holder with candle